Understanding and Optimizing the Patient Experience in Breast Reconstruction. Issue 2 (August 2016) - Cohen, Wess A.; Ballard, Tiffany N.S.; Hamill, Jennifer B.; Kim, Hyungjin M.; Chen, Xiaoxue; Klassen, Anne; Wilkins, Edwin G.; Pusic, Andrea L.
Abstract : Background: Optimizing the patient experience is a central pillar in healthcare quality. Although this may be recognized as important in breast reconstruction, surgeons are often unaware of how well they and members of their team achieve this goal. The objective of our study was to evaluate patient satisfaction with the experience of care in a multicenter, prospective cohort of patients undergoing breast reconstruction. Specifically, we sought to determine which aspects of the care experience might be most amenable to quality improvement. Methods: As part of the Mastectomy Reconstruction Outcomes Consortium Study, 2093 patients were recruited from 11 centers in North America. Of these, 1534 (73.3%) completed the BREAST-Q Satisfaction with Care scales (satisfaction with information, surgeon, medical team, and office staff) at 3 months after reconstruction and were included in the analysis. Results: Patients scored lowest on 'Satisfaction with Information' (mean = 72.8) compared to all other Satisfaction with Care scales (mean, 89.5-95.5). Patients with immediate reconstruction were less satisfied with their plastic surgeon compared to those with delayed reconstruction. The racial category, "Other" (Asians, Pacific Islanders, Hawaiians, American Indians), was the least satisfied group across all Satisfaction with Care scales. Conclusions: Patients undergoing breast reconstruction perceive significant gaps in their knowledge and understanding of expected outcomes. Immediate reconstruction patients and minority racial groups may require additional resources and attention. As a means to improve quality of care, these findings highlight an important unmet need and suggest that improving patient education may be central to providing patient-centered care.